Music as the finest disgust? A Kantian take on cacophony in the Critique of Judgement (Itinera, 2025)
The Kantian system of the fine arts notoriously places music at the bottom of the ladder; to be precise, it looks almost like it does not even deserve a place in the classification insofar as music, according to Kant, ought to be considered more an agreeable than a fine art. The aim of our paper is to inquire whether the peculiar status Kant ascribes to music can provide unique access to some issues of negative aesthetics that can be found in the Critique of Judgement: specifically, questions concerning the problem of the form of music as art in relation to its ability to cause unappealing as well as unwholesome feelings. Only those musical forms that preserve the formal purity of the instrument’s Ton seem to foreshadow the possibility of a music that claims for itself to be deemed more than just agreeable.
Keywords: Immanuel Kant; Critique of Judgement; Philosophy of music; 18th century German aesthetics